2018
DOI: 10.1039/c8ra07103a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced upconversion fluorescent probe of single NaYF4:Yb3+/Er3+/Zn2+ nanoparticles for copper ion detection

Abstract: Single-particle fluorescent probe for copper ion detection based on fluorescence quenching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Moreover, it has been shown that transition metal co-doped UCNPs can be used as fluorescent probes for the detection of heavy metal ions and biomolecules. For example, Zhang et al 130 found a ≥100 enhancement in the normally weak blue-band emission of 7 mol% Zn 2+ co-doped NaYF 4 :Yb 3+ ,Er 3+ nanoparticles, which could be a promising fluorescent probe for detecting Cu 2+ ions. In addition, for the determination of H 2 O 2 and uric acid (UA), a label-free fluorescence method was developed by Zhou et al 131 According to their research, this sensor can detect UA with a low detection limit and can be used to detect UA levels in human serum.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Moreover, it has been shown that transition metal co-doped UCNPs can be used as fluorescent probes for the detection of heavy metal ions and biomolecules. For example, Zhang et al 130 found a ≥100 enhancement in the normally weak blue-band emission of 7 mol% Zn 2+ co-doped NaYF 4 :Yb 3+ ,Er 3+ nanoparticles, which could be a promising fluorescent probe for detecting Cu 2+ ions. In addition, for the determination of H 2 O 2 and uric acid (UA), a label-free fluorescence method was developed by Zhou et al 131 According to their research, this sensor can detect UA with a low detection limit and can be used to detect UA levels in human serum.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Photon up-conversion (UC) is an anti-Stokes process in which the absorption of multiple low-energy photons leads to the emission of a photon with a higher energy than the excitation photon. [1][2][3][4][5][6][7] Rare-earth-doped up-conversion nanocrystals have garnered considerable attention because of their efficient energy transfer, good luminescence properties, and optical absorption ability, [8][9][10][11] which have signicant applications in the elds of solid-state laser, 12,13 multicolour display, 14,15 optical data storage, 16,17 optical communication, 18,19 and optical sensing. 20,21 Ye and co-worker discovered a new non-contact optical material Ba 3 Y 4 O 9 for temperature measurement, and they achieved high sensitivity over a wide measuring temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Various ions such as Li + (ionic radius 92 pm) 15 , Zn 2+ (90 pm) 16 , Na + (118 pm) 17 , and Bi 3+ (117 pm) 18 have been systematically investigated as both alio (oxygen imbalance) and homovalent (charge balanced) dopants. Especially, Li + and Zn 2+ co-doping has attracted considerable attention for a range of inorganic phosphors including fluorides [19][20][21] , binary oxides [22][23][24][25][26] , aluminates 27 , titanates 28,29 , and vanadates 16,[30][31][32][33] . It is reported that with optimized doping concentration, a large (≥10×) improvement in luminescence can be readily obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Zn 2+ co-doping was also observed to increase the UC emission in BaTiO 3 :Yb 3+ /Er 3+ nanophosphors as demonstrated by Mahata et al 37 The authors reported a 2× and 5× increase in the green and red emission bands, respectively, and attributed it to an increase in cell parameters (lattice expansion) by substitution of Zn 2+ at Ti 4+ sites. Recently, mol.% Zn 2+ co-doped NaYF 4 :Yb 3+ /Er 3+ nanoparticles 21 . This result is even more surprising considering that Zn 2+ co-doped particles were considerably smaller (~320 nm) compared with Zn 2+ -free phosphor (>1 µm).…”
Section: Introductionmentioning
confidence: 99%